Responding to the challenges of parenting a child with cerebral palsy: A focus group - Whittingham, K.; Wee, D.; Sanders, M.; Boyd, Roslyn (2011)
Purpose. To explore the unique parenting challenges that parents of children with cerebral palsy (CP) face and to explore the feasibility of a new parenting intervention, Stepping Stones Triple P (SSTP), for this population. Method. Focus groups were conducted with parents of children with CP (n = 8) and health professionals with experience in working with families of children with CP (n = 5). The discussion was transcribed verbatim and a descriptive thematic analysis was performed. Results. Parents stated that knowing whether a particular behaviour is the result of CP or a behavioural issue is challenging. Parents were also keen to promote communication, independence and socialisation in their child. In addition, parents also discussed the challenges of parenting under time pressure, with additional parenting tasks, under public scrutiny and with grief. Both parents and professionals found SSTP to be a feasible and appropriate intervention for parents of children with CP. Conclusions. The parents of children with CP in this study faced a range of parenting challenges that may be effectively targeted by a parenting intervention. In addition, parents and health professionals found SSTP content acceptable and feasible for use with parents of children with CP. © 2010 Informa UK, Ltd.